Ószövetségi teológia és ókori vallástörténet. A 11. zsoltár - KARASSZON, István (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2023)
Old Testament Theology and the Religion of the Ancient Near East The study discusses how mythical elements of the Ancient Near East have entered Old Testament theology and how they are placed within the statements of Old Testament faith. As an example, Psalm 11 is tackled with which originally was explained by exegetes as an individual lament. It turns out that the pivotal term, God’s throne, originated in the mythology of the Ancient Near East, but in its actual place it represents the presence of the God of Israel amongst His people.